Madrid, the Southeast Developments. The sun also rises - Maia, Camila; Kovacsova, Veronika; Kustermans, Clenn; Poulizac, Morgan; Sartori, Eleonora (AESOP, 2013)
The workshop aims to look at the landscape of the vacant and deserted territories on the city limits and think through what the nature of the actual situation is and venture into what the next steps forward could be. Within the socio economic context and with the framework of the revision of the Madrid Master Plan, the south-eastern fringe of the city presents a huge question mark. It is a place where planning is paralysed and poses a number of questions. What are the real problems that need to be solved once the speculative forces have faded away? What would be the role of the planner and the designer in such a territory? Should anything be done at all? Objectives: Research and development of possible strategies for a large area located in the city limits. Devising ways to approach this territory from different viewpoints. The objective is not so much to come up with a design but to think through possible strategies after grasping the complexity of the problems.
Strategies For the Post-Speculative City : Proceedings of the 4th AESOP European Urban Summer School, Madrid, Spain, September 2013